Synthesis, structure determination and characterization of novel organometallic chromium hexacarbonyl derivatives via ligand (L) substitution - Hamdya Farhana, Mohidin Yahya (2012)
The objective of the research study is to synthesize novel compounds through substitution process. The carbonyl ligand on chromium complexes is replaced by different tertiary phosphine ligands in order to produce a novel organometallic monocrystal compound. The crystal is characterized in terms of its structure, followed by the physical and chemical properties. Derivatives of Chromium Carbonyl are prepared by reaction with a number of tertiary phosphine ligands which have the potential to result in novel organometallic compounds. There are five attempt substitutions being done using Dicyclophenyiphosphene, Tris-(4fluorophenyl)phosphene, Tris-(3chlorophenyl)phosphine, Diphenylpentafluorophenyiphosphene and 1,2bis(dicyclohexylphosphino)ethane. From these, the substitution reaction using Tris-(4-fluorophenyl)phosphene resulted in the formation of a fine bright yellow crystal. From the monocrystal x-ray diffraction analysis, the resulting novel crystal structure is determined as Trans-bis[tris(4flourophenyl)phosphane]tetracarbonylchromium(0) with molecular formula C40H24CrF60 4P2. Infrared Spectroscopy ([R) and Nuclear Magnetic Resonance (NMIR) further compliment the X-ray diffraction results. For the novel structure, the Cr atom is octahedrally coordinated by four carbonyl ligands and two monodentate phosphorus ligands, which are bonded in a trans position to each other. The compound crystalizes in the monoclinic system, space group C2/c with an average Cr-P bond length of 2.3331 A and average Cr-CO bond length of 1.8808 A.